The Effectiveness of Couple Therapy Based on Acceptance and Commitment on the Quality of Marital Relationship and Adjustment - Fatemeh Ansari Haghighati (Universitas Ahmad Dahlan, 2020)
The aim of the current study is to investigate the effectiveness of couple therapy based on commitment and acceptance on the quality of marital relationships and adjustment of the couples of Bushehr. The statistical population of the current study includes all the couples, referring to the family consultation clinics in Bushehr in 2018. Using convenient sampling, 40 couples, referring to the consultation Aramesh clinic, Baran clinic, Mehr clinic in November and December, were randomly chosen and were appointed in two groups (20 in experimental groups and 20 in control group). The obtained data from the study were analyzed using covariance statistical analysis. The results indicated the effectiveness of couple therapy based on acceptance and commitment on the quality of marital relationship of the couples. It has been also effective on the permission of marital relationship, their satisfaction with marital relationship and tendency for marital relationship.Keywords: couple therapy based on commitment and acceptance, the quality of marital relationships, marital adjustment.Â